Charge convertibility and near infrared photon co-enhanced cisplatin chemotherapy based on upconversion nanoplatform. (June 2017) - Xu, Jiating; Kuang, Ye; Lv, Ruichan; Yang, Piaoping; Li, Chunxia; Bi, Huiting; Liu, Bin; Yang, Dan; Dai, Yunlu; Gai, Shili; He, Fei; Xing, Bengang; et al.
Abstract: Optimal nano-sized drug carrier requires long blood circulation, selective extravasation, and efficient cell uptake. Here we develop a charge-convertible nanoplatform based on Pt(IV) prodrug loaded NaYF4 :Yb, Tm upconversion nanoparticles (UCNs), followed by coating a layer of PEG-PAH-DMMA polymer (UCNs-Pt(IV)@PEG-PAH-DMMA). The polymer endows the platform with high biocompatibility, initial nano-size for prolonged blood circulation and selective extravasation. Especially, the anionic polymer can response to the mild acidic stimulus (pH ∼6.5) of tumor extracellular microenvironment and experience charge-shifting to a cationic polymer, resulting in electrostatic repulsion and releases of positive UCNs-Pt(IV). The positive UCNs-Pt(IV) nanoparticles have high affinity to negative cell membrane, leading to efficacious cell internalization. Simultaneously, the ultraviolet (UV) light emitted from UCNs upon near-infrared (NIR) light irradiation, together with the reductive glutathione (GSH) in cancer cells efficiently activate the Pt(IV) prodrug to highly cytotoxic Pt(II), realizing NIR photon improved chemotherapy. The experimental results reveal the charge convertibility, low adverse effect and markedly enhanced tumor ablation efficacy upon NIR laser irradiation of this smart nanoplatform. Moreover, combining the inherent upconversion luminescence (UCL) and computed tomography (CT) imaging capabilities, an alliance of cancer diagnosis and therapy has been achieved. Graphical abstract: